Pak-US Relations: An Overview in Historical Perspective (1947-2021) - Ali, Ishfaq; Anwar, Muhammad Fiaz (Pakistan Journal of Humanities and Social Sciences, 2023)
This comprehensive analysis explores the history of relations between the United States and Pakistan from the country's founding in 1947 to the year 2021, providing valuable context for understanding the complex nature of this diplomatic alliance. Through the use of a historical lens, the study investigates the major occasions, turning moments, and thematic developments that have influenced the bilateral relations between Pakistan and the US over time. Starting with the early years of diplomatic engagement, the examination looks at how Cold War dynamics affected Pakistan and the United States' alignment of interests in the early post-independence era. It explores the significance of Pakistan's role in enabling the U.S. and China to establish diplomatic relations in the 1970s and how it affected world geopolitics. The research also examines times of conflict and divergence, such as the 1960s military aid embargo, the 1980s nuclear proliferation worries, and the difficulties brought on by regional conflicts. A particular focus is placed on the period following 9/11, elucidating the intricacies of the strategic alliance established within the framework of the fight against terrorism and the consequent realignment of objectives. In addition, the abstract evaluates the relationship's economic aspects by looking at trade agreements, foreign aid, and how economic assistance shapes bilateral ties. It also takes into account how the internal political climates of both nations affect the ebb and flow of their interactions. This overview attempts to offer a comprehensive understanding of the persistent trends, difficulties, and opportunities that have shaped Pakistan-U.S. relations by utilizing a historical perspective. The study adds to a thorough examination of the diplomatic, geopolitical, economic, and sociocultural factors that have influenced the development of this important relationship over more than seven decades by using a multidimensional analysis.